Моделювання економічних систем в умовах підвищеного ризику - Вітлінський, Вальдемар Володимирович; Маханець, Любов Леонідівна (Тернопіль: ФОП Паляниця В. А., 2022)
The intensive development and widespread use of economic and mathematical models and methods of analysis and management of economic objects, processes, events taking into account the increasing range of risks and their degree is considered in this paper. The wide use of a number of systems and tools of artificial intelligence, economic dynamics, etc. is highlighted.
Simulation of economic systems in conditions of increased risk
Keywords: risk; model-algorithm-software system triad; system analysis of economic risk; situational modeling